The intellectual elites in EuroAmerica Imaginary Identitarians, men of letters, arts and sciences in Medellin and Antioquia, 1830-1920 (2004)
This research studies the history of “imaginary identity” in Colombia, particularly in the Antioquia area, through the texts and images that the intellectual elites, located in Medellín, produced between 1830 and 1920. We discovered the constant presence